Measurement and Analysis of The Development Level of Open Economy: A Case Study in Jiangsu Province - Zhang, Xueru; Yu, Jing (Transactions on Economics, Business and Management Research, 2024)
In recent years, the international landscape has rapidly evolved, presenting new challenges and opportunities for open economies. Using Jiangsu as a case study, this article assesses the province's open economy level through global factor and cluster analysis. Research has found that the overall development level of open economies in various cities has shown a tortuous growth trend, with significant regional differences between cities, indicating that the previous model of winning by quantity is no longer applicable. This article further analyzes the existing problems and provides relevant basis for policy improvement.